International HR Management: The Role of OCB Towards International HR Management Competency - Sunny, Mila Permata; Gede, I Komang; Maqsudi, Achmad; Sihwinarti, Dwi; Winda, Made (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
This study aims to analyze the role of HR Management and Organizational Citizenship Behavior (OCB) in shaping International Human Resource Management (IHRM) competencies, especially in cultural adaptation, cross-cultural communication, and international collaboration. The research method used is a quantitative approach with data collection through questionnaires distributed to HR professionals in multinational companies. The sample was selected using a purposive sampling technique, focusing on HR managers and HR professionals working in multinational companies that have implemented OCB programs. The collected data were analyzed using multiple linear regression. The results of statistical tests showed that a signifi cant relationship was found between HRM and OCB variables with IHRM competencies. Regression analysis indicated that 13.8% of the variation in IHRM competencies (R Square = 0.138) could be explained by these two independent variables. The regression coeffi cient for HRM was 0.139 with a p value = 0.041, while for OCB it was 0.231 with a p value = 0.004, indicating a positive and signifi cant contribution of both variables to improving IHRM competencies. The normality test shows that the residuals are normally distributed, and the multicollinearity test shows no signifi cant problems, with a Tolerance value of 0.974 and a VIF of 1.027. The conclusion of this study is that strengthening OCB in HR management strategies is very important for building and developing adaptive IHRM competencies, so that multinational companies can increase their competitiveness in the dynamic global market.